Photochromic Fluorescent Probe Strategy for the Super-resolution Imaging of Biologically Important Biomarkers - Chai, Xianzhi; Han, Hai-Hao; Sedgwick, Adam C; Li, Na; Zang, Yi; James, Tony D; Zhang, Junji; Hu, Xi-Le; Yu, Yang; Li, Yao; Wang, Yan; Li, Jia; et al. (Journal of the American Chemical Society, 2020)
Here, we report a β-galactosidase (β-Gal)-responsive photochromic fluorescent probe, NpG, that was designed to prebind to human serum albumin (HSA) to form the probe/protein hybrid, NpG@HSA. The formation of NpG@HSA led to an increase in fluorescence emission (520 nm) corresponding to the binding of the fluorescent naphthalimide unit with HSA. In addition, this enabled visualization of the spiropyran fluorescence emission in aqueous media. Our probe/protein hybrid approach afforded a unique imaging platform with enhanced cell permeability and solubility that was capable of visualizing the cellular uptake of NpG@HSA before its activation by β-Gal. The β-Gal-mediated cleavage of the galactose unit within the NpG@HSA hybrid resulted in the formation of NpM@HSA and an increase in red fluorescence emission (620 nm). The resultant merocyanine unit was then able to undergo photoisomerization (merocyanine ↔ spiropyran) to facilitate STORM (i.e., stochastic optical reconstruction microscopy) imaging with minimal phototoxicity and excellent photostability/reversibility. Using STORM, NpG@HSA was able to determine the subcellular distribution of β-Gal activity between cell lines with nanoscale precision. We believe that this system represents a versatile imaging platform for the design of photochromic fluorescent probes suitable for illuminating the precise location of disease-specific biomarkers in various cellular processes.